Frequency of occurrence of type 2 diabetes and metabolic disturbances in patients with schizophrenic range disorders with prolonged anti-relapse antipsychotic therapy (based on screening results) - L. N. Gorobets; M. A. Tsarenko; A. V. Litvinov; L. M. Vasilenko (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
The article presents the results of screening data from a simultaneous study of 443 outpatient cards of patients with schizophrenic spectrum disorders who were under dynamic outpatient monitoring in two areas of the psycho-neurological dispensary No. 2 in Moscow in order to assess the incidence of type 2 diabetes mellitus (T2DM), and also metabolic disorders (MD) in patients with prolonged anti-relapse antipsychotic therapy. The incidence of these disorders as a whole was 24.6%. Differences in the prevalence of diabetes mellitus 2 and MN were considered depending on the gender of the patient and the antipsychotic used. The obtained data on the high frequency of occurrence of the above metabolic disorders indicate the need to develop standards for antipsychotic therapy of patients with schizophrenic spectrum disorders when combined with T2DM and MD.